2008
DOI: 10.1682/jrrd.2007.04.0058
|View full text |Cite
|
Sign up to set email alerts
|

Effective methods of pelvic plexus nerve and bladder stimulation in anesthetized animal model

Abstract: Abstract-Urinary retention is a serious urological problem associated with spinal cord injuries (SCIs) and other pelvic disorders. Effective methods of pelvic nerve stimulation were investigated for this problem. Following anesthesia in five dogs, the bladder was surgically exposed. Bladder and anal sphincter pressures were recorded. Testing was first conducted with probe electrodes. Barb electrodes were then implanted with a needle near the pelvic plexus nerves and the bladder wall. We tested different electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…In our prior of cats and dogs studies we observed higher bladder pressures to stimulation [14][15][16][17][18][19]. In our most recent study of dogs, we used similar but fewer bipolar barb electrodes on the bladder wall than were used in this study.…”
Section: Problem With the Animal Modelmentioning
confidence: 97%
See 4 more Smart Citations
“…In our prior of cats and dogs studies we observed higher bladder pressures to stimulation [14][15][16][17][18][19]. In our most recent study of dogs, we used similar but fewer bipolar barb electrodes on the bladder wall than were used in this study.…”
Section: Problem With the Animal Modelmentioning
confidence: 97%
“…For the remaining four animals, we made replica bipolar electrodes ( Fig. 1) modeled after the bipolar Permaloc TM electrodes [14]. The replica electrodes consisted of multistranded, stainless-steel wires insulated with Teflon ® (Model X, Cooner wire Inc, Chatworth, CA) in which five mm of Teflon R insulation was stripped from the end of the lead and then was bent back over a 20 G needle to create a barb electrode.…”
Section: Electrodesmentioning
confidence: 99%
See 3 more Smart Citations